Could TREM-1 be a novel marker in the diagnosis of fibromyalgia?: A cross-sectional study - Baykara, Rabia Aydogan; Kiran, Tugba Raika; Otlu, Onder; Erdem, Mehmet; Tas, Nevsun Pihtili (Lippincott Williams & Wilkins, 2024)
Triggering receptors expressed on myeloid cells-1 (TREM-1) are transmembrane molecules expressed in cells of the immune system. Activation of TREM-1 leads to the release of pro-inflammatory mediators, which act as amplifiers of inflammation and thereby contribute to the pathogenesis of various diseases, whether inflammatory or not. This study explored the role of TREM-1 in the etiopathogenic context of fibromyalgia syndrome (FMS) and its association with disease activity. This randomized controlled and observational study included 45 patients diagnosed with FMS according to the 2016 American College of Rheumatology criteria. Serum TREM-1 levels were assessed using ELISA, and disease activity was measured using various scales such as the fibromyalgia impact questionnaire (FIQ). Patients were divided into 2 groups according to disease severity based on the FIQ score. Compared to a control group of 46 healthy individuals, patients with FMS exhibited significantly elevated concentrations of TREM-1 (mean +/- SD = 216.97 pg/mL +/- 16.04), P < .05. The FIQ, Pittsburgh sleep quality index, hospital anxiety and depression scale, fatigue severity scale, and visual analog scale, which confirm symptoms such as pain, disease severity, sleep disturbance, depression, anxiety, and fatigue seen in FMS was significantly correlated with TREM-1 level (P < .001). The optimal threshold value for TREM-1 to disease activity was determined to be 182.250, showing (area under the curve) (CI (95%)): [0.940] (0.887-0.993), a sensitivity of 97% and a specificity of 89% according to the receiver operating characteristic analysis. The positive correlation of TREM-1 with various symptom severity scales and hematological inflammatory indices may be a suitable biomarker for the diagnosis of FMS and a potential therapeutic target.
Keywords: biomarker; fibromyalgia impact questionnaire; fibromyalgia syndrome; hematological and inflammatory indices; TREM-1